Mesenchymal Epithelial Transition Factor Signaling in Pediatric Nervous System Tumors: Implications for Malignancy and Cancer Stem Cell Enrichment - Khater, Amanda Rose; Abou-Antoun, Tamara (Frontiers in Cell and Developmental Biology, 2021)
Malignant nervous system cancers in children are the most devastating and worrisome diseases. specifically due to their aggressive nature and in some cases, inoperable location in critical regions of the brain and spinal cord and the impermeable blood brain barrier that hinders delivery of pharmaco-therapeutic compounds into the tumor site. Moreover, the delicate developmental processes of the nervous system throughout the childhood years adds another limitation to the therapeutic modalities and doses used to treat these malignant cancers. Therefore, pediatric oncologists are charged with the daunting responsibility of attempting to deliver effective cures to these children, yet with limited doses of the currently available therapeutic options in order to mitigate the imminent neuro-toxicity of radio- and chemo-therapy on the developing nervous system. Various studies reported that c-MET/HGF signaling is affiliated with increased malignancy and stem cell enrichment in various cancers such as high grade gliomas, high-risk medulloblastomas and MYCN -amplified, high-risk neuroblastomas. Therapeutic interventions that are utilized to target c-MET signaling in these malignant nervous system cancers have shown benefits in basic translational studies and preclinical trials, but failed to yield significant clinical benefits in patients. While numerous pre-clinical data reported promising results with the use of combinatorial therapy that targets c-MET with other tumorigenic pathways, therapeutic resistance remains a problem and long-term cures are rare. The possible mechanisms, including the over-expression and activation of compensatory tumorigenic mechanisms within the tumors or ineffective drug-delivery methods that may contribute to therapeutic resistance observed in clinical trials are elaborated in this review.